Mutational analysis of Portuguese families with multiple endocrine neoplasia type 1 reveals large germline deletions. - Cavaco, B; Domingues, R; Bacelar, M; Cardoso, H; Barros, L; Gomes, L; Ruas, M; Agapito, A; Garrão, A; Pannett, A; Silva, J; Sobrinho, L; et al. (2002)
OBJECTIVE: To determine the spectrum of MEN1 mutations in Portuguese kindreds, and identify mutation-carriers. PATIENTS, DESIGN AND RESULTS: Six unrelated MEN1 families were studied for MEN1 gene mutations by single-strand conformational polymorphism (SSCP) and DNA sequence analysis of the coding region and exon-intron boundaries of the MEN1 gene. These methods identified 4 different heterozygous mutations in four families: two mutations are novel (mt 1539 delG and mt 655 ims 11 bp) and two have been previously observed (mt 735 del 46p and mt 1656 del C) all resulting in a premature stop codon. In the remaining two families, in whom no mutations or abnormal MEN1 transcripts were detected, segregation studies of the 5' intragenic marker D11S4946 and codon 418 polymorphism in exon 9 revealed two large germline deletions of the MEN1 gene. Southern blot and tumour loss of heterozygosity analysis confirmed and refined the limits of these deletions, which spanned the MEN1 gene at least from: exon 7 to the 3' untranslated region, in one family, and the 5' polymorphic site D11S4946 to exon 9 (obliterating the initiation codon), in the other family. Twenty-six mutant-gene carriers were identified, 6 of which were asymptomatic. CONCLUSIONS: These results emphasize the importance of the detection of MEN1 germline deletions in patients who do not have mutations of the coding region. Important clues indicating the presence of such deletions may be obtained by segregation studies using the intragenic polymorphisms D11S4946 and at codon 418. The detection of these mutations will help in the genetic counselling of clinical management of the MEN1 families in Portugal.